Transgender preventative health—chest/breast cancer screening - Bacot-Davis, Valjean R.; Moran, Allison H. (Frontiers in Health Services, 2024)
Cancer mortality rates have decreased over the last 48 years attributable to standardized cancer screenings. These screenings were developed without deliberate inclusion of transgender and non-binary populations. While specialists are familiar regarding cancer screening in this distinct population, those in primary care might be more limited. As such, we aimed to develop a screening risk tool that combines the Breast Cancer Risk Assessment Tool (Gail model) with the updated American College of Radiology Appropriateness Criteria—Transgender Breast Cancer Screening, into an online questionnaire designed to accommodate primary care physicians performing routine health screenings to advise appropriate imaging and referral for this population. This new tool can be used for transgender chest/breast risk assessment whereas the Gail model alone was developed without transgender populations in mind, with the aim of early detection and cancer prevention in this historically underserved healthcare population.